2020
DOI: 10.3233/jad-200752
|View full text |Cite
|
Sign up to set email alerts
|

Data-Driven Modeling of Knowledge Assemblies in Understanding Comorbidity Between Type 2 Diabetes Mellitus and Alzheimer’s Disease

Abstract: Background: Recent studies have suggested comorbid association between Alzheimer’s disease (AD) and type 2 diabetes mellitus (T2DM) through identification of shared molecular mechanisms. However, the inference is pre-dominantly literature-based and lacks interpretation of pre-disposed genomic variants and transcriptomic measurables. Objective: In this study, we aim to identify shared genetic variants and dysregulated genes in AD and T2DM and explore their functional roles in the comorbidity between the disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…Taken together, these clinical observations suggest a correlation between both processes, which we aimed to analyze by superimposing the two KGs of both pathophysiologies [42,54]. We overlayed Heme KG with COVID-19 KG to identify similarities, as successfully shown in the earlier reported approach for type II Diabetes and Alzheimer's disease [50,51,53]. Indeed, the results of the knowledge-driven analysis revealed a core of similar shared molecular patterns.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Taken together, these clinical observations suggest a correlation between both processes, which we aimed to analyze by superimposing the two KGs of both pathophysiologies [42,54]. We overlayed Heme KG with COVID-19 KG to identify similarities, as successfully shown in the earlier reported approach for type II Diabetes and Alzheimer's disease [50,51,53]. Indeed, the results of the knowledge-driven analysis revealed a core of similar shared molecular patterns.…”
Section: Discussionmentioning
confidence: 87%
“…This knowledge gap can be addressed by using custom-made models, such as Knowledge Graphs (KGs) [50]. Placing research data in the right context by employing KGs supports the elucidation of biochemical mechanisms, the generation of novel hypotheses, and the identi cation of targets for drug repurposing [50][51][52][53]. Two of our recent scienti c publications focused on KGs around heme as well as COVID-19 [42,54].…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, these clinical observations suggest a correlation between both processes, which we aimed to analyze by superimposing the two KGs of both pathophysiologies [ 42 , 54 ]. We overlayed the Heme KG with the COVID-19 KG to identify similarities, as successfully shown in the earlier reported approach for type II diabetes and Alzheimer’s disease [ 50 , 51 , 53 ]. Indeed, the results of the knowledge-driven analysis revealed a core of similar shared molecular patterns.…”
Section: Discussionmentioning
confidence: 99%
“…This knowledge gap can be addressed by using custom-made models such as knowledge graphs (KGs) [ 50 ]. Placing research data in the right context by employing KGs supports the elucidation of biochemical mechanisms, the generation of novel hypotheses, and the identification of targets for drug repurposing [ 50 , 51 , 52 , 53 ]. Two of our recent scientific publications focused on KGs around heme as well as COVID-19 [ 42 , 54 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many experiments suggested that impaired metabolism in obesity, overweight, or type 2 diabetes mellitus (T2DM) influences the physiological actions of the brain, such as memory and cognitive function [ 6 , 7 ]. Adipose tissue regulates metabolism and energy balance throughout the body and is a significant targeted therapy for metabolic syndrome.…”
Section: Introductionmentioning
confidence: 99%